Evaluasi Program CSR (Corporate Social Responsibility) Perusahaan PT. ANTAM Tbk UBPN SULTRA Kecamatan Pomalaa Kabupaten Kolaka (Studi Kasus Desa Tambea) - Theofilus Salea; Irfan Ido (Universitas Halu Oleo, 2019)
ABSTRACTTPT. ANTAM Tbk is a company engaged in the exploration of mining materials such as nickel, gold and silver, and bauxite. Tambea village is one of the areas in Pomalaa Subdistrict, Kolaka Regency, which is close to PT. ANTAM Tbk. The purpose of this study can evaluate the CSR program of PT. ANTAM Tbk in Tambea Village, Pomalaa District, Kolaka Regency. The method of determining the sample uses the System of Rising Intensification method with a population of 24 heads of households as respondents. The analytical method used to determine the relationship between the level of performance and level of expectation is the method of IPA analysis (Importance-Performance Analysis). The results of this study indicate that the company PT. ANTAM Tbk still has to improve its performance on the elements of program distribution and supporting elements of the program. Keywords: Evaluation, CSR Program and company PT. ANTAM Tbk.